Top Executive Compensation in less Developed Capital Markets - Pereira, Ivo; Esperança, J. (5th European Conference on Management, Leadership and Governance, 2009)
Purpose–This paper aims to study the determinants of variable compensation for top Portuguese executives (chief executive officers, chief financial officers and commercial directors). Design/methodology/approach–Data from 101 firms were collected through an email questionnaire sent to the human resource directors of 500 largest and best Portuguese firms of Exame, a business newspaper. A Tobit regression analysis was used to estimate the basic equation of the study. Findings–The conclusions are generally consistent with findings obtained in more developed capital markets. It was found that public and older corporations are more intensive users of variable pay, consistent with the agency theory prediction. A location in the centre of economic activity and a higher executive education increase the propensity to receive higher levels of salary in the form of variable compensation. The relation between compensation and performance was more elusive. Research limitations/implications–There are limitations as to the extrapolation of the obtained results, as the level of potential idiosyncrasy cannot be measured. Ideally, the study should be replicated in different contexts to control for country-specific influences. Nevertheless, the main finding that performance-related pay mechanisms are less used in countries where public corporations and potential agency problems are less pervasive should hold. Originality/value–As the focus is on a small economy with a developing capital market, this paper contributes to executive compensation literature that has mostly analysed firms based in well-developed capital markets, with a higher separation of ownership and control (Anglo-Saxon countries).